2010
DOI: 10.1029/2010ja015873
|View full text |Cite
|
Sign up to set email alerts
|

Rise and fall of electron temperatures: Ohmic heating of ionospheric electrons from underdense HF radio wave pumping

Abstract: [1] Here we present electron temperature variations observed with incoherent scatter radar during a European Incoherent Scatter Scientific Association Heating experiment with high-frequency (HF) radio wave transmission at frequencies above the peak ionospheric critical frequency. The electron temperature increased from 2000 K up to 2800 K during the HF transmission periods. During the experiment both pump frequency and polarization were altered between pump pulses. The observed temperature variation is compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…As seen in Figure 2a during the second period we expect very weak D/E region absorption and thus significant F-region heating. Furthermore the data indicate under-dense probably collisional F-region heating similar to the one discussed by Gustavsson et al [2010]. Figure 2c also shows maximum amplitude at 12 Hz, and 1/f behavior at higher frequencies as seen in the amplitude of the ELF triplets (12-18-24) and (28-36-44).…”
Section: Experimental Observationssupporting
confidence: 75%
“…As seen in Figure 2a during the second period we expect very weak D/E region absorption and thus significant F-region heating. Furthermore the data indicate under-dense probably collisional F-region heating similar to the one discussed by Gustavsson et al [2010]. Figure 2c also shows maximum amplitude at 12 Hz, and 1/f behavior at higher frequencies as seen in the amplitude of the ELF triplets (12-18-24) and (28-36-44).…”
Section: Experimental Observationssupporting
confidence: 75%
“…Heating in underdense conditions at Tromsø has been modeled by Gustavsson et al [2010] and good agreement between observations and theory was found on the basis that the heating is due to the electric field of the electromagnetic pump wave alone. However, Gustavsson et al [2010] did not explicitly quantify the efficiency of this mechanism, which is of interest here. In the present work, experimental data in which the pump power was systematically varied are analyzed to determine the electron heating rate as a function of available radio wave power flux and hence the efficiency of the heating mechanism.…”
Section: Introductionmentioning
confidence: 89%
“…The relationship between the electron heat source and the available pump power for overdense F‐region heating has been examined before in a number of cases [ Mantas et al , 1981; Robinson , 1989; Stocker et al , 1992]. Heating in underdense conditions at Tromsø has been modeled by Gustavsson et al [2010] and good agreement between observations and theory was found on the basis that the heating is due to the electric field of the electromagnetic pump wave alone. However, Gustavsson et al [2010] did not explicitly quantify the efficiency of this mechanism, which is of interest here.…”
Section: Introductionmentioning
confidence: 99%
“…Löfas et al [2009] and Gustavsson et al [2010] employed the electric field model of Shoucri and Morales [1984] which can be used to estimate the electric field of a pump wave at any altitude as it approaches reflection and found it to be reliable at modeling the electron temperature as measured by an incoherent scatter radar.…”
Section: Electric Field Modelmentioning
confidence: 99%